Endothelial Dysfunction - Old Concepts and New Challenges 2018
DOI: 10.5772/intechopen.73024
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Senescence in the Pathogenesis of Endothelial Dysfunction

Abstract: Aging is the main risk factor for cardiovascular diseases (CVD), and senescence in endothelial cells seems to be an initial step in the cascade of events that will culminate with the development of these pathologies. In this chapter, we examine the pathophysiological mechanism(s) involved in endothelial senescence, leading to CVD as well as the biochemical and cellular pathways that may explain the activation and development of the process of endothelial senescence, and we discuss new hypotheses supported by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 126 publications
(138 reference statements)
2
24
0
1
Order By: Relevance
“…Accordingly, the results of our previous study show that both strands of miR-126 are encapsulated in endothelial MVs, and that vascular endothelial repair is mediated by miR-126 and HIF-1α . Results reported that miRNAs are involved in the senescence phenotype acquisition (Alique et al, 2017Carracedo et al, 2018b). Several miRNAs-mediated pathological effects are described in Table 3.…”
Section: Vsmcs Contractility and Proliferationmentioning
confidence: 99%
“…Accordingly, the results of our previous study show that both strands of miR-126 are encapsulated in endothelial MVs, and that vascular endothelial repair is mediated by miR-126 and HIF-1α . Results reported that miRNAs are involved in the senescence phenotype acquisition (Alique et al, 2017Carracedo et al, 2018b). Several miRNAs-mediated pathological effects are described in Table 3.…”
Section: Vsmcs Contractility and Proliferationmentioning
confidence: 99%
“…Cellular aging or cellular senescence is a process that occurs naturally in our cells when we age, due to persistent exposure to cellular stressors [11]. Senescent cells are characterized by a permanent state of cell cycle arrest accompanied by a secretory phenotype and resistance to cell death [11]. When a senescent phenotype becomes dysfunctional, the ability to maintain homeostasis between living and dead cells is lost.…”
mentioning
confidence: 99%
“…The current characterization of senescent cells includes the evaluation of molecular senescence markers, such as p53, p21, p16, and γ-H2AX, as well as telomere attrition, which are enhanced signals for senescence-associated beta-galactosidase (SA-β-gal). These markers are indirect indicators because the activation of these pathways is simply one piece of evidence that cells are senescent [11]. Interestingly, once the p16 pathway is activated, senescence arrest cannot be reversed by the inactivation of p53 or the silencing of p16 [16].…”
mentioning
confidence: 99%
“…Los datos recogidos en la literatura avalan a la senescencia endotelial como uno de los eslabones iniciales de la cadena de eventos que conducen a senescencia y daño vascular, con el subsecuente desarrollo de ECV [76,77]. Dado que las MV endoteliales producidas por células senescentes pueden actuar como mecanismo patogénico en la disfunción endotelial, y puesto que está ampliamente demostrado su papel como sistema de señalización intercelular, era lógico pensar que podían participar promoviendo el daño en otras estructuras vasculares además del propio endotelio [78].…”
Section: Microvesículas Endoteliales Senescentes Como Promotores De La Senescencia Vascularunclassified